1988
DOI: 10.1016/0009-2509(88)80049-6
|View full text |Cite
|
Sign up to set email alerts
|

Rate enhancements and quasi-periodic dynamics during forced concentration cycling of CO and O2 over supported PtSnO2

Abstract: Forced reactant cycling of carbon monoxide-nitrogen and oxygen-nitrogen streams over Pt-SnO, in a differential reactor results in enhancements of the reaction rate of up to 9 times that of the optimal steady state. Dynamic features common to periodically forced reaction systems were experimentally observed. In addition, quasi-periodic behaviour under forced concentration cycling was also observed. Transient response experiments combined with see-through FTIR analysis confirm an underlying Langmuir-Hinshelwood-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…One way to perturb the catalytic oxidation process in order to increase the CO 2 production is by switching the external pressure back and forth across the discontinuous transition y 2 (k) [5,6,7,8,9]. It has been shown that when the ZGB system without desorption is quickly oscillated between the low and high θ CO phases by a periodic variation of the external pressure, there is considerable enhancement of the catalytic activity [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…One way to perturb the catalytic oxidation process in order to increase the CO 2 production is by switching the external pressure back and forth across the discontinuous transition y 2 (k) [5,6,7,8,9]. It has been shown that when the ZGB system without desorption is quickly oscillated between the low and high θ CO phases by a periodic variation of the external pressure, there is considerable enhancement of the catalytic activity [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Positive results were in fact reported in a number of studies conducted typically under atmospheric pressure conditions [6][7][8][9][10]. Under these conditions mass and heat transfer plays a dominant role contrary to the low pressure ( p < 10 −3 mbar) single crystal experiments in which periodic forcing was also investigated.…”
Section: Introductionmentioning
confidence: 90%
“…Non-stationary reaction conditions may im-prove the yield and selectivity of reactions or reduce energy consumption as compared to stationary conditions [4][5][6]. oxidation of CO and unburned hydrocarbons as well as NO reduction [6][7][8][9][10]. In heterogeneous catalysis experimental studies with periodic forcing focused on the reactions of the automotive catalytic converter, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] In heterogeneous catalysis, periodic forcing has mostly been applied to reactions which play a role in the automotive catalytic converter, and in some cases substantial increases of the efficiency have been reported. [10][11][12][13] Periodic forcing experiments have been conducted in catalytic CO oxidation under high-pressure conditions (pϾ1 mbar). 11,15 Single crystal experiments have been performed for catalytic CO oxidation on Pt͑100͒ and Pt͑110͒.…”
Section: Introductionmentioning
confidence: 99%